inverse functions

posted by .

1-3cos=sin squared

You need to define the variables, such as x, y etc.
If you are trying to solve
1 - 3 cos x = sin^2 x for whatever x is, then you are not talking about an inverse function.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. trig

    Reduce the following to the sine or cosine of one angle: (i) sin145*cos75 - cos145*sin75 (ii) cos35*cos15 - sin35*sin15 Use the formulae: sin(a+b)= sin(a) cos(b) + cos(a)sin(b) and cos(a+b)= cos(a)cos(b) - sin(a)sin)(b) (1)The quantity …
  2. tigonometry

    expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b) …
  3. math

    Can anyone help w/ these. 1) Solve the equation in the internal [0deg, 360deg]. a) sin 2x = -sin x b) sin 2T = -1/2 (where T is angle) c) 4 sin^2T = 3 2) Evaluate the expression. sin(arctan 2) 3) Rewrite the following w/o using trigonometric …
  4. algebra

    Can someone please help me do this problem?
  5. pre-cal

    Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos 6x can be expressed as a series of terms that involve sin x or cos x only, but the end result is not a simplification. sin 2x = 2 sinx cosx cos 6x = 32 cos^6 x -48
  6. Mathematics - Trigonometric Identities

    Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) = (sin^2y …
  7. TRIG!

    Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 …
  8. Calculus

    Use a trig identity to combine two functions into one so you can solve for x. (The solution should be valid for any value of t). 3cos(t) + 3*sqrt(3)*sin(t)=6cos(t-x) I know that 6 cos(t-x) can be 6(cos(t)cosx(x)+sin(t)sin(x)) I don't …
  9. Precalculus with Trigonometry

    Prove or disprove the following Identities: cos(-x) - sin(-x) = cos(x) + sin (x) sin raised to the 4 (theta) - cos raised to the 4 (theta) = sin squared (theta) - cos squared (theta) cos (x+(pi)/(6)) + sin (x - (pi)/(3)) = 0 cos(x+y)cos(x-y) …
  10. Trigonometry

    Solve the equation for solutions in the interval 0<=theta<2pi Problem 1. 3cot^2-4csc=1 My attempt: 3(cos^2/sin^2)-4/sin=1 3(cos^2/sin^2) - 4sin/sin^2 = 1 3cos^2 -4sin =sin^2 3cos^2-(1-cos^2) =4sin 4cos^2 -1 =4sin Cos^2 - sin=1/4 …

More Similar Questions